Analisis Mikrobiologi Kue Buayo Berendam: Studi Eksperimen pada Makanan Tradisional Jambi - Saffana Aura Balqis; Ardi Mustakim (Polygon : Jurnal Ilmu Komputer dan Ilmu Pengetahuan Alam, 2025)
Kue buayo berendam is a traditional food from Jambi that is unique in terms of ingredients, taste, and processing method. This food is made from glutinous rice flour and coconut milk, which gives it a chewy texture and a savory and sweet taste. With the increasing interest in functional foods that are not only delicious but also beneficial for health, kue buayo berendam has the potential for further study, especially in terms of its microbial content. One interesting aspect to study is the presence of lactic acid bacteria (LAB), especially from the genus Lactobacillus, which is known to have probiotic benefits. This study aims to identify the presence of Lactobacillus spp. in kue buayo berendam to determine the probiotic potential of this traditional food. The methodology used in the study included bacterial isolation from cake samples, observation of colony morphology, Gram staining to determine the type of bacterial cell wall, and a series of biochemical tests to identify the characteristics of the bacteria found. From the results of isolation and identification, it was found that most of the bacteria successfully cultured were Lactobacillus spp., which are Gram-positive and rod-shaped bacteria. The presence of Lactobacillus spp. The results of the research on kue buayo berendam (soaked crocodile cake) indicate that this food not only has cultural and flavor value but also has the potential to be a source of natural probiotics. Probiotics are known to play a role in maintaining digestive health, boosting the immune system, and balancing the gut microbiota. Therefore, kue buayo berendam (soaked crocodile cake) can be further developed as a traditional functional food that supports public health. These findings open up opportunities to enhance the nutritional and health value of local fermented foods, while preserving regional culinary heritage in more innovative and value-added forms.